Harnessing immersive technologies for enhancing mathematical logics education in secondary schools - Velychko, V. Ye.; Fedorenko, E. G.; Kaidan, N. V.; Kaidan, V. P.; Кайдан, Н. В.; Кайдан, В. П. (CEUR Workshop Proceedings, 2024)
The majority of information that individuals perceive throughout their lifetimes is received through the perception of visual images, a rule that applies to the performance of any activity. Consequently, failing to consider the visual presentation of new knowledge during the learning process, as well as its quality, can hinder new generations from receiving a quality education. Considering current realities and demands on knowledge, skills, and abilities acquired during training, the issue of using high-quality visual educational content is closely linked to the development and use of information and communication technologies. This work examines and analyses the current state of the use of immersive technologies in education and explores the possibilities and specifics of employing virtual worlds in the educational process. Practical results of approbating virtual tools in the educational process are provided. A pedagogical experiment aimed at determining the effectiveness of immersive technologies in the context of the Ukrainian education system has been initiated.
Keywords: mathematical logics; immersive technologies; learning tools; virtual worlds; gamification; secondary education